Tumor size and invasiveness matters for partial nephrectomy: external validation and modification of the arterial based complexity score - Kriegmair, Maximilian; Hetjens, Svetlana; Budjan, Johannes; Michel, Maurice Stephan; Pfalzgraf, Daniel Philipp; Wagener, Nina (Journal of surgical oncology, 2017)
Background: Outcome of partial nephrectomy (PN) depends on anatomic features of the renal tumor, which can be assessed by nephrometry scores. The aim was to externally validate and refine the Arterial Based Complexity (ABC) score and to compare it to established systems. Methods: Tumors of 300 patients undergoing PN were categorized according to the ABC, RENAL, and PADUA score. Size and tumor invasiveness were combined to form the ABCD score. Correlation analysis and multivariate logistic regression was performed to validate and compare the respective scores as predictors of surgical outcome. Results: The ABC score shows significant correlation with ischemia time (IT) (P < 0.01), opening of the collecting system (CS) (P < 0.01), and conversion to nephrectomy (P = 0.01). In the multivariate analysis, the ABC score was predictive for on-clamp excision (P < 0.01) and opening of the CS (P < 0.01) only. The RENAL and ABCD scores were independent predictors for complications (P = 0.02, P = 0.05), IT (P < 0.01, P = 0.03), on clamp excision (P < 0.01, P < 0.01), and opening of the CS (P < 0.01, P < 0.01). Conclusions: The ABC score correlates well with surgical parameters. Expanding the score by tumor diameter gives the ABCD system. It has similar predictive effectiveness to the well-established RENAL score, but features simplicity by only assessing invasiveness and tumor size.